Mapping the History of Ayurveda : Culture, Hegemony and the Rhetoric of Diversity - Girija, K. P. (Abingdon, Oxon ; New York : Routledge, 2022)
This book looks at the institutionalisation and refashioning of Ayurveda as a robust, literate classical tradition, separated from the assorted, vernacular traditions of healing practices. It focuses on the dominant perspectives and theories of indigenous medicine and various compulsions which led to the codification and standardisation of Ayurveda in modern India. Critically engaging with authoritative scholarship, the book extrapolates from some of these theories, raising significant questions on the study of alternative knowledge practices. By using case studies of the southern Indian state of Kerala - which is known globally for its Ayurveda -it provides an in-depth analysis of local practices and histories. Drawing from interviews of practitioners, archival documents, vernacular texts and rare magazines on Ayurveda and indigenous medicine, it presents a nuanced understanding of the relationships between diverse practices. It highlights the interactions as well as the tensions within them, and the methods adopted to preserve the uniqueness of practices even while sharing elements of healing, herbs and medicine. It also discusses how regulations and standards set by the state have estranged assorted healing practices, created uncertainties and led to the formation of categories like Ayurveda and nattuvaidyam (indigenous medicine/ayurvedas). Lucid and topical, the book will be useful for researchers and people interested in social medicine, history of medicine, Ayurveda, cultural studies, history, indigenous studies, andsocial anthropology.
Keywords: Medicine, Ayurvedic -- History; Medicine, Ayurvedic -- India -- Kerala; Ethnology -- India -- Kerala; Kerala (India) -- Social life and customs; HISTORY / Asia / India & South Asia; HISTORY / Historiography; HISTORY / Social History